Gold nanocluster-based ratiometric fluorescent probe for biosensing of Hg2+ ions in living organisms. Issue 12 (23rd May 2022) - Yu, Fanfan; Xiang, Hui; He, Shiyu; Zhao, Gan; Cao, Zheng; Yang, Lina; Liu, Honglin
Abstract : A gold nanocluster-based dual-emission fluorescent nanoprobe for ratiometric sensing and imaging of Hg 2+ ions in living organisms. Abstract : Gold nanoclusters (Au NCs) have become a new alternative to conventional fluorescent probes in biosensing and imaging. Herein, a gold nanocluster-based nanocomplex displaying single-excitation and dual-emission fluorescence property was fabricated by the conjugation of red-emitting glutathione-protected gold nanoclusters (Au-GSH NCs) and green-emitting fluorescein isothiocyanate (FITC) molecules. The inorganic–organic nanocomplex possesses good ratiometric fluorescence sensing ability with one emission peak showing a sensitive fluorescence response towards Hg 2+ ions and the other acting as the internal reference. The nanocomplex was demonstrated to have high stability, excellent biocompatibility, high intracellular penetrability and good biological imaging ability. It was employed as a sensitive nanosensor for rapid sensing and imaging of Hg 2+ ions in living cells and zebrafish with high contrast.